Current occupational well‐being status and protective and risk factors of male nurses in Chengdu, China: A cross‐sectional study - Liang Wang; Huiling Li; Xinyu Li; Jia Zhang; Yu Lv; Ping Jia; Caixia Xie (Wiley, 2022)
Abstract Aims This study explores the current occupational well‐being status of male nurses in Chengdu, China, and identifies the concomitant protective and risk factors. Design This study has a cross‐sectional survey design. Methods From 13 July to 21 July 2019, a cross‐sectional survey involving 209 male nurses in 7 tertiary hospitals in Chengdu, China, was conducted using a general information questionnaire, the Mindfulness Attention Awareness Scale, the Acceptance and Action Questionnaire‐II, the Professional Identity Scale and the Nurses' Occupational Well‐being Scale. Results The score of male nurses' occupational well‐being was 78.7 ± 14.2. The higher the mindfulness and professional identity (p = .002, p < .001, respectively), the higher the occupational well‐being of male nurses. The lower the experiential avoidance, the higher the occupational well‐being (p = .001). The highest occupational well‐being was found among male nurses who had less than 5‐years' working experience. Conclusions The results suggest that male nurses' occupational well‐being was at a moderate level. Mindfulness and professional identity were the protective factors of male nurses' occupational well‐being, and experiential avoidance was the risk factor. Nursing managers should ascertain male nurses' current occupational well‐being and the influencing factors and formulate effective improvement strategies. Male nurse courses on enhancing mindfulness and professional identity and reducing experiential avoidance should be explored, with a focus on helping nurses improve their professional well‐being and, in turn, prospectively reducing the turnover rate.